Studi Ekologi dan Pemanfaatan Vegetasi untuk Konservasi Air di Beberapa Sumber Mata Air Desa Jak Kabupaten Timor Tengah Utara - Remigius Binsasi; Willem Amu Blegur; Yolanda Getrudis Naisumu; Polikarpia W. Bani; Jefrianus Sanan (Jurnal Ekologi, Masyarakat dan Sains, 2026)
This study examines vegetation ecology around the springs of Jak Village as part of an effort to understand vegetation dynamics and its role in sustaining water resources. The research aims to analyze the distribution of stem diameter classes of each species, community structure based on density, frequency, basal area, and Importance Value Index (IVI), the influence of environmental factors on vegetation growth, and forms of community empowerment. The quadrat method was applied using 200-meter transects at three springs—Oe’aniut, Oe’naek, and Oe’ana—with five observation plots established at each site. Vegetation data included tree, pole, sapling, and seedling growth forms, while environmental parameters comprised air temperature, air humidity, soil pH, and soil moisture. The results indicate variation in diameter class distribution among locations. The highest IVI values were recorded for the tree stratum of Syzygium samarangense (36.01%), pole stratum of Areca catechu (79.57%), sapling stratum of Tectona grandis (68.91%), and seedling stratum of Syzygium samarangense (22.60%). It is concluded that vegetation plays a crucial role in spring conservation, supported by active community participation through reforestation activities.